Influence of Canva Media Based on Guided Inquiry Model on Students' Critical Thinking Ability and Chemical Literacy - Evi Nuridah Pulungan; Khairul Fahmi Simamora (Universitas Negeri Medan, 2024)
The rapid development of science and technology in the 21st century also signals that education or schools are expected to be able to produce graduates who have critical thinking skills and scientific literacy skills to be able to adapt to various challenges in 21st century life. This research aims to analyze the influence of the application of model-based Canva media guided inquiry towards students' critical thinking abilities and chemical literacy. The sample in this study were students or cadets of class The instruments used in this research were critical thinking ability tests and chemical literacy ability tests on organic compounds. The research data were analyzed using the one-way MANOVA technique. The results of the research concluded that: (1) there is an influence of the application of Canva media based on a partial guided inquiry model on students' critical thinking abilities; (2) there is a partial influence of Canva media based on the guided inquiry model on students' chemical literacy abilities; and (3) there is an influence of Canva media based on the guided inquiry model simultaneously on students' critical thinking skills and chemical literacy skills.